The Relationship between Principal Supervision and Kindergarten Teacher Performance in Nusaniwe District, Ambon City - Rosmaryn Tutupary (International Journal of Education, Information Technology, and Others, 2021)
Purpose of this study is to describe the existence of a positive and significant relationship between principal supervision and work motivation with the performance of kindergarten teachers in Nusaniwe District, Ambon City. The research design contains the substance of the approach and the type of research with the implications of the analysis technique. The results showed that the supervision of the principal can be described through the highest score of 90 and the lowest score of 60 with an average of 77.34 and mode of 77.42, teacher performance can be described through the highest score of 90 and the lowest score of 65 with an average of 79.05 and mode 78.5, there is a significant relationship between supervision and teacher performance of 0.88.